Alloreactive Natural Killer Cells for the Treatment of Acute Myeloid Leukemia: From Stem Cell Transplantation to Adoptive Immunotherapy - Ruggeri, Loredana; Parisi, Sarah; Urbani, Elena; Curti, Antonio (Frontiers in Immunology, 2015)
Natural killer (NK) cells express activating and inhibitory receptors, which recognize MHC class-I alleles, termed “Killer cell Immunoglobulin-like Receptors” (KIRs). Preclinical and clinical data from haploidentical T-cell-depleted stem cell transplantation have demonstrated that alloreactive KIR-L mismatched NK cells play a major role as effectors against acute myeloid leukemia (AML). Outside the transplantation setting, several reports have proven the safety and feasibility of NK cell infusion in AML patients and, in some cases, provided evidence that transferred NK cells are functionally alloreactive and may have a role in disease control. The aim of the present work is to briefly summarize the most recent advances in the field by moving from the first preclinical and clinical demonstration of donor NK alloreactivity in the transplantation setting to the most recent attempts at exploiting the use of alloreactive NK cell infusion as a means of adoptive immunotherapy against AML. Altogether, these data highlight the pivotal role of NK cells for the development of novel immunological approaches in the clinical management of AML.